PERANCANGAN SISTEM SMART ATTENDANCE DAN MONITORING RUANGAN KELAS BERBASIS ESP32 - Roihan Parli Lubis; Rianda Sapitra Lubis; Muhammad Ikbal; Dian Putra Saragi; Eka Dodi Suryanto (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid development of Internet of Things (IoT) and embedded systems has significantly transformed conventional manual systems into automated and integrated solutions. One of the critical applications is in attendance systems and environmental monitoring, which are still commonly implemented manually and prone to errors, data manipulation, and inefficiency. This study aims to design and implement a smart attendance system integrated with classroom environmental monitoring using the ESP32 microcontroller. The system utilizes an RFID RC522 module for user identification, a DHT11 sensor for temperature and humidity monitoring, a PIR sensor for motion detection, and an LDR sensor for light intensity measurement. The collected data are processed by the ESP32 and displayed in real-time through a 16×2 LCD interface, while actuators such as a DC fan, buzzer, and LED indicators respond automatically based on system conditions. The research methodology includes hardware and software design, system integration, and performance testing. A threshold-based control algorithm with hysteresis is implemented to ensure stable fan operation and avoid frequent switching. Experimental results indicate that the system successfully performs accurate RFID-based attendance recording, real-time environmental monitoring, and automatic fan control when the temperature exceeds the defined threshold. The integration of multiple sensors enhances system functionality and improves energy efficiency. Therefore, the proposed system can be considered a reliable prototype for smart classroom applications that combines attendance automation and environmental control in a single platform.